Amplitude–frequency relationship to a fractional Duffing oscillator arising in microphysics and tsunami motion. Issue 3 (December 2019) - Wang, Yan; An, Jian-Ye
Fractional oscillators can effectively deal with noise in the vibration. This paper adopts He's fractional derivative, which is defined through the variational iteration algorithm. Ji-Huan He's amplitude–frequency formulation is used to solve the fractional Duffing equation.